Use of Bichat’s adipose body as a graft to treat gingival recession - Falcón Guerrero, Britto Ebert (2021)
Objective. Review was to gather scientifc evidenceon the clinical results obtained by using the Bichat’s adipose body (BAB) in the treatment of gingival recessions. Methods. The PubMed, Cochrane and Wiley Online Library databases were reviewed. Using the followingsearch terms: “buccal” AND “adipose tissue” OR “fat pad” AND “coverage” AND “gingival recession”. By combining searches and fltering only documents that contain the English-language review target, only 9 articles that meet the inclusion criteria were generated. Results. The information found, where pediculated and free grafts with the Bichat’s adipose body were used, was analyzed, fnding good results in all cases; which means that this is a good autologous alternative for the treatment of gingival  recessions, in the face of the limitations of palate grafts. Conclusions. The use of Bichat’s adipose body is a promising autologous proposal and represents a good alternative for the success of the treatment of gingival recessions.